Computer-aided drug design and virtual screening of targeted combinatorial libraries of mixed-ligand transition metal complexes of 2-butanone thiosemicarbazone. (August 2018) - Khan, Tahmeena; Ahmad, Rumana; Azad, Iqbal; Raza, Saman; Joshi, Seema; Khan, Abdul Rahman
Graphical abstract: Highlights: The study deals with in silico evaluation of mixed ligand complexes in terms of their druglikeness, toxicity and bioactivity score. Multivariate data were analyzed by Principal Component Analysis in OSIRIS software. Docking results yielded best scores with 2-picoline complexes. Four mixed ligand complexes of Fe were synthesized and characterized using NMR, IR and UV spectroscopy. [FeL(2-pic)2 ], [FeL(bpy)], [FeL(py)2 ] exhibited significant anticancer activity against breast and lung cancer cell lines. Abstract: The present paper deals with in silico evaluation of 32 virtually designed transition metal complexes of 2-butanone thiosemicarbazone and N, S, O containing donor hetero-ligands namely py, bpy, furan, thiophene, 2-picoline, 1, 10-phenanthroline, piperazine and liquid ammonia. The complexes were designed with a view to assess their potential anticancer, antioxidant and antibacterial activity. The absorption, distribution, metabolism, excretion and toxicity (ADMET) properties of the chosen ligands were calculated by admetSAR software. Metabolic sites of different ligands likely to undergo metabolism were predicted using Metaprint 2D. The proposed complexes were also evaluated for their drug-like quality based on Lipinski's, Veber, Ghose and leadlikeness filters. Druglikeness and toxicity potential were predicted by OSIRIS property explorer. The pharmacokinetic properties and bioactivity scores were calculated by Molinspiration tool. Bioactivity scores of the complexes were predicted for drug targets including enzymes, nuclear receptors, kinase inhibitors, G-protein coupled receptor ligands and ion channel modulators. Molecular docking of selected Fe(II) mixed-ligand complexes was performed using AutoDock version 4.2.6 and i-GEMDOCK version 2.1 with two target proteins namely Ribonucleotide reductase (RR) and Topoisomerase II (Topo II). The results were compared with three standard reference drugs viz . Doxorubicin HCl, Letrozole (anticancer) and Tetracycline (antibiotic). Multivariate data obtained were analyzed using principal component analysis (PCA) for visualization and projection as scatter and 3D plots. Positive results obtained for hetero-ligands using admetSAR version 1.0 indicated good absorption and transport kinetics of the hetero-ligand complexes through the human intestine and blood-brain barrier. The hetero-ligands were predicted to have no associated mutagenic effect(s) also. However, none of the hetero-ligands was predicted to be Caco-2 (human colon cancer cell line) permeable. Most of the hetero-ligands and the parent ligand (2-butanone thiosemicarbazone) were predicted to undergo Phase-I metabolism prior to excretion using MetaPrint2D software. Pharmacokinetic evaluation of the proposed complexes revealed that all complexes displayed drug-like character and were predicted to have no apparent toxic side-effects. All the proposed complexes showed moderate to good biological activity scores (−5.0 to 0.0). Mixed complexes with bpy, 2-picoline and 1, 10-phenanthroline showed significant bioactivity scores (as enzyme inhibitors) in the range 0.02–0.13. Likewise, good docking scores were obtained for Fe (II) complexes with the same ligands. [FeL(2-pic)2 ] displayed the lowest binding energy (−6.47 kcal/mol) with respect to Topo II followed by [FeL(py)2 ] (−6.14 kcal/mol) as calculated by AutoDock version 4.2.6. With respect to binding with RR, [FeL(2–pic)2 ] again displayed the lowest binding energy (−7.21 kcal/mol) followed by [FeL(py)2 ] (−5.96 kcal/mol). On the basis of docking predictions and various other computational evaluations, four mixed-ligand complexes of Fe in +2 oxidation state with py, bpy, 2–picoline and 1, 10-phenanthroline were synthesized with 2-butanone thiosemicarbazone. All the synthesized Fe complexes were characterized using various spectroscopic techniques and tested for their potential anticancer activity in vitro against human breast carcinoma cell line MDA-MB 231 and human lung carcinoma cell line A549 cell line using MTT assay. [FeL(2-pic)2 ], [FeL(bpy)], and [FeL(py)2 ] were found to exhibit significant antiproliferative activity with IC50 values in the range of 80–100 μM against breast and lung cancer cells. The synthesized Fe complexes also displayed mild antioxidant activities. The synthesized and studied Fe complexes have the potential for development into future anticancer agents if analyzed and modified further for improvement of their ADMET, solubility and permeability criteria set for potential drug-candidates.